Combining clinical and magnetic resonance imaging markers enhances prediction of 12-year disability in multiple sclerosis - Uher, Tomas; Vaneckova, Manuela; Sobisek, Lukas; Tyblova, Michaela; Seidl, Zdenek; Krasensky, Jan; Ramasamy, Deepa; Zivadinov, Robert; Havrdova, Eva; Kalincik, Tomas; Horakova, Dana (Multiple sclerosis (Houndmills, Basingstoke, England), 2017)
BACKGROUND: Disease progression and treatment efficacy vary among individuals with multiple sclerosis. Reliable predictors of individual disease outcomes are lacking. OBJECTIVE: To examine the accuracy of the early prediction of 12-year disability outcomes using clinical and magnetic resonance imaging (MRI) parameters. METHODS: A total of 177 patients from the original Avonex-Steroids-Azathioprine study were included. Participants underwent 3-month clinical follow-ups. Cox models were used to model the associations between clinical and MRI markers at baseline or after 12 months with sustained disability progression (SDP) over the 12-year observation period. RESULTS: At baseline, T2 lesion number, T1 and T2 lesion volumes, corpus callosum (CC), and thalamic fraction were the best predictors of SDP (hazard ratio (HR) = 1.7-4.6; p ⩽ 0.001-0.012). At 12 months, Expanded Disability Status Scale (EDSS) and its change, number of new or enlarging T2 lesions, and CC volume % change were the best predictors of SDP over the follow-up (HR = 1.7-3.5; p ⩽ 0.001-0.017). A composite score was generated from a subset of the best predictors of SDP. Scores of ⩾4 had greater specificity (90%-100%) and were associated with greater cumulative risk of SDP (HR = 3.2-21.6; p < 0.001) compared to the individual predictors. CONCLUSION: The combination of established MRI and clinical indices with MRI volumetric predictors improves the prediction of SDP over long-term follow-up and may provide valuable information for therapeutic decisions.
Keywords: dospělí; Magnetic Resonance Imaging; Female; biologické markery; Biomarkers; lesions; Adult; ženské pohlaví; Disability Evaluation; magnetic resonance imaging; Predictive Value of Tests; prediktivní hodnota testů; lidé; Multiple Sclerosis; magnetická rezonanční tomografie; roztroušená skleróza; interferon beta 1a; následné studie; mozek; disability; atrofie; Follow-Up Studies; Male; progrese nemoci; brain atrophy; Atrophy; Brain; Interferon beta-1a; Disease Progression; posuzování pracovní neschopnosti; predictors; lidé středního věku; mužské pohlaví; Multiple sclerosis; Middle Aged; Humans